Attention differentially modulates the coupling of fMRI BOLD and evoked potential signal amplitudes in the human somatosensory cortex. - Arthurs, O; Johansen-Berg, H; Matthews, P; Boniface, S (2004)
Blood oxygenation dependent contrast (BOLD) fMRI is used increasingly to probe "connectivity" based on temporal correlations between signals from different brain regions. This approach assumes that there is constant local coupling of neuronal activity to the associated BOLD response. Here we test the alternative hypothesis that there is not a fixed relationship between these by determining whether attention modulates apparent neurovascular coupling. Electrical stimulation of the median nerve was applied with and without a concurrent distractor task (serial subtraction). Increasing stimulation intensity increased discomfort ratings ( p<0.001) and was associated with a significant increase in both somatosensory evoked potential (SEP) N20-P25 amplitude and BOLD fMRI response in the contralateral primary (SI) and bilaterally in the secondary somatosensory cortices. Attention to stimulation was reduced during distractor task performance and resulted in an overall trend for reduction in discomfort ( p=0.056), which was significant at the highest stimulation level ( p<0.05). A volume of interest analysis confined to SI confirmed a reduction in BOLD response with distraction ( p<0.001). However, distraction did not measurably affect SEP magnitude. The quantitative relationship between the BOLD fMRI response and the local field potential measured by the early SEP response therefore varies with attentional context. This may be a consequence of differences in either local spatial or temporal signal summation for the two methods. Either interpretation suggests caution in assuming a simple, fixed relationship between local BOLD changes and related electrophysiological activity.